Noah Scape Can't Stop Repeating Himself - Bass, Guy (Edinburgh: Barrington Stoke Ltd, 2021)
Getting what you want isn't always what you need in this laugh-out- loud comedy from one of the fastest-rising stars of the children's book world Guy Bass. Particularly suitable for struggling, reluctant or dyslexic readers aged 8+
Keywords: Children's stories